WKB ameliorates DSS-induced colitis through inhibiting enteric glial cells activation and altering the intestinal microbiota - Qi Sun; Bai-Rong Li; Dong-Hao Li; Xiao-Ying Wang; Qian-Yi Wang; Zhi-Meng Jiang; Shou-Bin Ning; Tao Sun (Journal of Translational Medicine)
Abstract Background Inflammatory bowel disease (IBD) is a chronic condition influenced by diet, which affects gut microbiota and immune functions. The rising prevalence of IBD, linked to Western diets in developing countries, highlights the need for dietary interventions. This study aimed to assess the impact of white kidney beans (WKB) on gut inflammation and microbiota changes, focusing on their effects on enteric glial cells (EGCs) and immune activity in colitis. Methods Male C57BL/6 mice were divided into four groups: normal diet (ND), ND with 2.5% dextran sulfate sodium (DSS) for colitis induction, ND with 20% WKB, and WKB with 2.5% DSS. The dietary intervention lasted 17 weeks, with DSS given in the final week. Colonic inflammation was assessed by body weight, disease activity index, and histopathology. Epithelial barrier integrity was evaluated using immunofluorescence, transmission electron microscopy, and permeability assays. EGCs activity was analyzed via immunofluorescence and quantitative real-time PCR. Immune responses were measured using flow cytometry and cytokine profiling, while gut microbiota changes were examined through metagenomic sequencing. Results WKB supplementation significantly alleviated DSS-induced colitis in mice, evidenced by reduced weight loss, disease activity, and improved colonic histology. This effect was linked to enhanced mucosal barrier integrity, seen through increased tight junction protein and Muc2 expression, accompanied by favorable ultrastructural changes. WKB modulated EGCs activity via TNF-like cytokine 1 A inhibition, resulting in reduced glial fibrillary acidic protein expression. Immunologically, it downregulated Th1 and Th17 pro-inflammatory cells, increased Treg cells, and altered cytokine profiles (reduced TNF-α, IFN-γ, IL-17; increased IL-10). Metagenomic analysis showed that WKB restored gut microbiota balance, particularly enhancing beneficial bacteria like Akkermansia. KEGG pathway analysis further indicated that WKB supplementation improved key metabolic pathways, notably those related to phenylalanine, tyrosine, and tryptophan biosynthesis, thereby countering DSS-induced metabolic disruptions. Conclusions WKB shows promise for treating IBD by enhancing mucosal barriers, inhibiting EGCs activity, balancing Th1/Th17/Treg cells, and restoring gut microbiota and metabolic homeostasis, thereby alleviating colitis symptoms.